Gall bladder emptying in normal subjects–a data base for clinical cholescintigraphy. Issue 2 (February 1987) - Mackie, C R; Baxter, J N; Grime, J S; Hulks, G; Cuschieri, A
Abstract : Biliary excretion scintigraphy with a cholagogic test meal may be used to assess patients with suspected disorders of gall bladder motility. The interpretation of results is frustrated, however, by the lack of information about the range of normal responses in a form suitable for comparative analysis. We present the results of 41 gall bladder emptying studies on 32 normal healthy subjects (14 men, 18 women) 30 minutes after intravenous injection of 74 MBq 99Tcm-EHIDA. Gall bladder emptying was provoked by the ingestion of 300 ml milk. Gamma camera scintigraphy was used to plot gall bladder activity against time. Gall bladder emptying occurred within 10 minutes in all men and 12/18 women (p = 0.02). Gall bladder ejection fractions were significantly greater in women (p less than 0.05). Duplicate studies in nine subjects showed good reproducibility (r = 0.959). A plot of mean and (m + 2 SD) values of gall bladder activity against time has been derived. The data provide an estimate of normal gall bladder emptying response, which may be used to aid interpretation of clinical studies.